2.) f (x) = 3x - 8 Step 1: Change f(x) to y y = 3x - 8 Step 2: replace every x with y and every y with x x = 3y - 8 Step 3: Transpose y x + 8 / 3 = 3y / 3 Step 4: Divide both side by x -1 y = x + 8 / 3 Step 5: Replace y with F-1(X) f-1 = x + 8 /3
Now i understand how to solve this equation.
11 Humss - 1 Group 4
Hand shows up and writes the steps on solving the first one to one problem . Voice Over: " The first step on solving one to one functions is first .... and thats it."
Student smiles and understands on solving one to one and inverse functions.